Functional current collector and preparation method thereof
By spraying inorganic nanoparticle solution on the surface of the metal layer of the functional current collector and drying it, the problem of residual stress during magnetron sputtering is solved, and the characteristics of low stress, high stability and mechanical strength of the functional current collector are achieved, thereby improving the battery performance.
Patent Information
- Application Number
- CN202510238655.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-03
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-03-03
AI Technical Summary
The existing functional current collectors are prone to residual stress during magnetron sputtering, resulting in increased risk of film stress deformation and metal layer shedding after electroplating, affecting battery performance.
The inorganic nanoparticle solution is sprayed on the surface of the metal layer of the base film, and the inorganic nanoparticles are dried and used to change the microstructure of the metal layer by using the high specific surface area and surface activity of the inorganic nanoparticles, increasing defects and dislocations, and serving as stress concentration points to disperse and release stress.
It effectively reduces the residual stress of the functional current collector, improves its stability and mechanical strength, reduces the risk of metal layer falling off, and thus improves the cycle life and energy density of the battery.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of current collectors, and in particular to a functional current collector and a preparation method thereof. Background Art
[0002] With the rapid development of new energy and electronic technology, higher requirements are placed on the cycle life, safety performance, and energy density of batteries. As a very important part of the battery, the current collector is used to collect the current generated by the active materials in the battery to form a larger current output. Its performance will directly affect the cycle life, energy density, safety performance, etc. of the battery.
[0003] At present, the positive and negative electrodes in the battery mostly use copper foil and aluminum foil as current collectors. This type of current collector has high cost and quality, which is not conducive to controlling battery costs and improving energy density. Compared with traditional foil as current collector, composite foil has obvious advantages. Composite foil current collectors are usually a "sandwich" structure, with a polymer high molecular layer on the inner layer and metal conductive layers on both sides. Since the functional current collector has a thinner metal layer on the surface and a lighter polymer layer inside, it can greatly reduce the overall weight of the functional current collector, thereby improving the energy density of the battery. At the same time, the thinner metal layer on the surface of the functional current collector is easier to disconnect than the traditional foil current collector when the battery thermal runaway occurs, thereby isolating the connection between the active material and the current collector and preventing the battery thermal runaway from continuing.
[0004] Although functional current collectors have the advantages of low cost and light weight, residual stress is easily generated in the current production process of functional current collectors, especially in the process of preparing the metal layer by magnetron sputtering. The residual stress can cause stress deformation of the film after electroplating, increase the risk of metal layer falling off, and thus deteriorate the performance of the battery. Summary of the invention
[0005] In order to solve the problem that the existing functional current collector is prone to generate residual stress during magnetron sputtering and reduce the residual stress of the functional current collector, the present invention provides a functional current collector and a preparation method thereof.
[0006] According to a first aspect of the present invention, a method for preparing a functional current collector is provided, the method comprising the following steps: S1. Plating a metal layer on at least one surface of the base film by magnetron sputtering; S2. Spraying an inorganic nanoparticle solution on the surface of the metal layer to obtain a semi-finished product; S3. Dry the semi-finished product to obtain a functional current collector.
[0007] In the preparation method of the functional current collector provided by the present invention, a metal layer is plated on the surface of a base film by magnetron sputtering, and then an inorganic nanoparticle solution is sprayed on the surface of the metal layer and dried to obtain a functional current collector. Since the inorganic nanoparticles have a high specific surface area and surface activity, the inorganic nanoparticles contained in the inorganic nanoparticle solution can form good contact and interaction with the surface of the metal layer and change the microstructure of the metal layer during the process of spraying the inorganic nanoparticle solution on the surface of the metal layer, thereby increasing the number of defects and dislocations on the surface of the metal layer. These defects and dislocations can serve as stress concentration points, so that the stress of the functional current collector is dispersed and released at these positions, thereby reducing the overall stress level of the functional current collector. In addition, the interface bonding force between the inorganic nanoparticles and the metal layer is weak. During the spraying process or when subjected to other external stresses, the inorganic nanoparticles are prone to slight sliding and deformation at the interface between the inorganic nanoparticles and the metal layer, which is conducive to absorbing or releasing stress and can play a good buffering role. In summary, in the preparation process of the functional current collector, the present invention can effectively release stress from the aspects of microstructure and interface characteristics by spraying an inorganic nanoparticle solution on the surface of the metal layer, thereby achieving the purpose of reducing the residual stress of the functional current collector and improving the stability and mechanical strength of the functional current collector.
[0008] Preferably, in S2, the inorganic nanoparticles in the inorganic nanoparticle solution include at least one of nano-silicon dioxide, nano-aluminum oxide, nano-iron powder and nano-nickel powder.
[0009] Preferably, in S2, the inorganic nanoparticles in the inorganic nanoparticle solution include at least one of nano-silicon dioxide and nano-aluminum oxide.
[0010] Compared with nano-iron powder and nano-nickel powder, the chemical properties of nano-silicon dioxide and nano-aluminum oxide used in the inorganic nanoparticle solution are less active, which can reduce the oxidation or unnecessary chemical reactions with the metal layer during use that affect the performance of the functional current collector. In addition, nano-silicon dioxide and nano-aluminum oxide have higher specific surface area and surface activity, which is beneficial to enhance the contact and interaction between nano-silicon dioxide, nano-aluminum oxide and the metal layer, thereby improving the stress dispersion and release effect of the functional current collector.
[0011] Preferably, the particle size of the inorganic nanoparticles is 10-20 nm.
[0012] Inorganic nanoparticles with a particle size within the above range have good dispersibility, moderate surface activity, and good penetration and filling capabilities. In the preparation process of the functional current collector, the particle size of the inorganic nanoparticles used in the inorganic nanoparticle solution is controlled within the above range. Firstly, the uniform distribution of the inorganic nanoparticles on the surface of the metal layer can be ensured. Secondly, it can ensure that the inorganic nanoparticles effectively interact with the surface of the metal layer of the functional current collector to play the role of stress release, and can reduce the risk of instability or over-reaction of the inorganic nanoparticles due to the excessive surface activity of the inorganic nanoparticles. Thirdly, it can penetrate into the microstructure of the functional current collector to a certain extent, fill the tiny gaps therein, and enhance the overall structural stability and mechanical strength of the functional current collector.
[0013] If the particle size of the inorganic nanoparticles used in the inorganic nanoparticle solution is too small, during the preparation process of the functional current collector, the surface energy of the inorganic nanoparticles with too small a particle size is too high, and their stability in the solvent is reduced, and they are prone to agglomeration or precipitation. In addition, too small a particle size will make the penetration depth of the inorganic nanoparticles in the functional current collector too great, which will make it difficult for the inorganic nanoparticles to play a stress release role in the metal layer; if the particle size of the inorganic nanoparticles used in the inorganic nanoparticle solution is too large, during the preparation process of the functional current collector, the inorganic nanoparticles with too large a particle size have poor dispersion performance in organic solvents, and are prone to agglomeration in the solvent, resulting in reduced uniformity of the inorganic nanoparticles, thereby affecting the distribution uniformity of the inorganic nanoparticles on the surface of the metal layer of the functional current collector and the effect of stress release. In addition, inorganic nanoparticles with too large a particle size will affect the uniformity of the microstructure of the functional current collector, thereby affecting its overall performance.
[0014] Preferably, the material of the base film is selected from at least one of polyethylene terephthalate (PET) film, polypropylene (PP) film, and polyimide (PI) film.
[0015] Preferably, in S2, the mass fraction of the inorganic nanoparticles in the inorganic nanoparticle solution is 5-15%.
[0016] During the preparation of the functional current collector, the mass fraction of the inorganic nanoparticles in the inorganic nanoparticle solution is controlled within the above range, which can not only provide sufficient stress concentration points and defects on the surface of the metal layer, so that the residual stress generated in the preparation of the functional current collector can be well dispersed and released, but also make the inorganic nanoparticles evenly dispersed in the solution, so that the inorganic nanoparticles can be evenly attached to the surface of the metal layer during the process of spraying the inorganic nanoparticle solution on the surface of the metal layer, thereby improving the residual stress release effect of the functional current collector.
[0017] If the mass fraction of inorganic nanoparticles in the inorganic nanoparticle solution is too low, firstly, the number of stress concentration points and defects provided by the inorganic nanoparticles will be insufficient, making it difficult to effectively disperse and release the stress generated by the functional current collector during the preparation process, thereby making it difficult to achieve the ideal stress release effect. Secondly, too few inorganic nanoparticles will make it difficult to fully change the microstructure of the functional current collector, so that its hindering effect on the regular arrangement of metal atoms in the metal layer of the functional current collector is not obvious, and its effect on reducing the accumulation of internal stress is limited, which leads to an unsatisfactory residual stress reduction effect of the functional current collector. If the mass fraction of inorganic nanoparticles in the inorganic nanoparticle solution is too high, firstly, it is easy to cause the nanoparticles to agglomerate in the solution, making it difficult to disperse evenly. The agglomerated inorganic nanoparticles are difficult to evenly cover the surface of the metal layer of the functional current collector, affecting the stress release effect of the functional current collector finally obtained. Secondly, too many inorganic nanoparticles will increase the viscosity of the inorganic nanoparticle solution, making it difficult to evenly adhere to the surface of the metal layer of the functional current collector during the spraying process, thereby leading to uneven local stress release of the functional current collector finally obtained.
[0018] Preferably, in S2, the solvent in the inorganic nanoparticle solution includes at least one of ethanol and acetone.
[0019] Compared with water or other organic solvents such as ethyl acetate or xylene, the inorganic nanoparticle solution used in the preparation process of the functional current collector uses ethanol and / or acetone as solvent. Ethanol and acetone have certain volatility but do not evaporate too quickly. In the process of spraying the inorganic nanoparticle solution with ethanol and / or acetone as solvent on the surface of the metal layer, the volatilization of the solvent will cause the inorganic nanoparticles to be evenly distributed on the surface of the metal layer. These evenly distributed inorganic nanoparticles can effectively hinder the regular arrangement of metal atoms in the metal layer and reduce the accumulation of internal stress.
[0020] If water is used as a solvent to prepare an inorganic nanoparticle solution, due to the large surface tension of water, it is difficult for the inorganic nanoparticles to be evenly distributed on the surface of the metal layer during the preparation of the functional current collector, resulting in agglomeration of the inorganic nanoparticles, making it difficult to effectively penetrate and cover the surface of the metal layer. In addition, water is a non-volatile solvent, and its residue in the functional layer will affect the electrochemical properties of the functional current collector and subsequent processing technology.
[0021] If ethyl acetate is used as a solvent to prepare an inorganic nanoparticle solution, due to the high volatility of ethyl acetate, the inorganic nanoparticles will aggregate together too quickly before the solvent completely evaporates during the preparation of the functional current collector, making it difficult for the inorganic nanoparticles to be evenly distributed on the surface of the metal layer. This will cause the action range of the inorganic nanoparticles to be reduced and uneven, making it difficult to effectively reduce the overall stress level of the final functional current collector.
[0022] If xylene is used as a solvent to prepare an inorganic nanoparticle solution, due to the weak volatility of xylene, the inorganic nanoparticles are difficult to compound and fix on the surface of the metal layer in a timely manner during the preparation of the functional current collector, affecting the stress release effect of the functional current collector. In addition, excessive residual xylene will affect the electrochemical properties of the functional current collector and have an adverse effect on subsequent processing.
[0023] Preferably, in S3, after the semi-finished product is dried, the method further comprises the step of washing the dried semi-finished product with a washing liquid; the washing liquid contains a surfactant, and the surfactant includes fatty alcohol polyoxyethylene ether.
[0024] After the inorganic nanoparticle solution is sprayed on the surface of the metal layer and dried, the solvent in the inorganic nanoparticle solution will evaporate. After the inorganic nanoparticles play a stress release role in the metal layer and its surface, the inorganic nanoparticles attached to the metal layer are not necessary for the subsequent application of the functional current collector. A large number of residual inorganic nanoparticles may affect the product performance of the functional current collector in the actual application process. This scheme uses a cleaning solution containing a surfactant, fatty alcohol polyoxyethylene ether, to clean the dried semi-finished product. The hydrophilic polyoxyethylene ether chain and the hydrophobic fatty alcohol chain in the fatty alcohol polyoxyethylene ether interact with the inorganic nanoparticles and the metal layer, which can reduce the interfacial tension between the metal layer and the inorganic nanoparticles, reduce the adhesion of the inorganic nanoparticles, and make the inorganic nanoparticles easily detach from the metal layer and stably dispersed in the cleaning solution, thereby achieving the purpose of removing the inorganic nanoparticles on the metal layer and its surface, and ensuring the product performance of the functional current collector finally prepared in the actual application process.
[0025] Preferably, the cleaning operation conditions are as follows: time 10-20 s, temperature 20-25°C.
[0026] Preferably, in S1, along a direction away from the base film, the metal layer includes a nickel-chromium alloy layer and a copper layer which are compounded in sequence.
[0027] During the preparation of the functional current collector, a nickel-chromium alloy layer is first composited on the surface of the base film, and then a copper layer is composited on the nickel-chromium alloy layer. Both the nickel-chromium alloy layer and the copper layer serve as metal layers. By setting a nickel-chromium alloy layer between the base film and the copper layer as a connection, the nickel-chromium alloy layer has a higher affinity with the base film and a higher molecular bond bonding ability, which can improve the bonding force between the base film and the copper layer, thereby improving the mechanical strength of the functional current collector.
[0028] Preferably, the thickness of the nickel-chromium alloy layer is 5-15 nm.
[0029] In the process of preparing the functional current collector, controlling the thickness of the nickel-chromium alloy layer used to connect the base film and the copper layer within this range is conducive to ensuring good bonding between the copper layer and the base film. If the thickness of the nickel-chromium alloy layer is too small, it will be difficult to provide sufficient bonding force, and the copper layer and the base film will be easily separated, thereby affecting the stability and reliability of the functional current collector; if the thickness of the nickel-chromium alloy layer is too large, the resistance of the functional current collector will increase, and its conductive performance will be reduced, thereby affecting the charge and discharge efficiency and energy density of the battery using the functional current collector.
[0030] According to a second aspect of the present invention, a functional current collector is provided. The functional current collector is prepared by the above-mentioned method for preparing the functional current collector.
[0031] The functional current collector prepared by the method provided by the present invention has the characteristics of low residual stress, high stability and mechanical strength. DETAILED DESCRIPTION
[0032] The following is a further clear and complete description of the technical features in the technical solution provided by the present invention in conjunction with the specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0033] Example 1 A functional current collector is prepared by the following steps: (1) Equipment preparation Prepare a high vacuum winding magnetron sputtering equipment to ensure the normal operation of the equipment, and prepare a water electroplating line to ensure its normal operation; (2) Target preparation Choose nickel-chromium alloy and copper with smooth surface and no impurities as target materials; (3) Basement membrane preparation A PP film with a thickness of 4 μm and a smooth surface without impurities is selected as the base film 1; (4) Magnetron sputtering Starting a magnetron sputtering device, using a nickel-chromium alloy as a target material to plate a nickel-chromium alloy layer with a thickness of 10 nm on both surfaces of the base film, and then using copper as a target material to plate a copper layer with a thickness of 50 nm on the surface of the nickel-chromium alloy layer, the nickel-chromium alloy layer and the metal layer are collectively referred to as a metal layer; (5) Water electroplating After the base film with a metal layer on the surface is placed on the electroplating machine, a basic electroplating solution is added and the copper layer with a thickness of 50 nm prepared by magnetron sputtering is thickened to 1 μm by using a water electroplating process; Among them, the basic electroplating solution contains copper acid solution and additives A / B; The copper acid solution was purchased from Dongyouyue (Suzhou) Electronic Technology New Materials Co., Ltd. The copper acid solution contains hydrochloric acid, copper sulfate solution and sulfuric acid solution. The concentration of hydrochloric acid is 40-70 g / L, the concentration of copper sulfate solution is 70-130 g / L, and the concentration of sulfuric acid solution is 100-140 g / L. Additives A / B were purchased from Suzhou Jeremy Chemical Company. Additive A is a leveling agent, and its specific ingredients include tetrahydrothiazolethione, polyethyleneimine alkyl compound, fatty amine ethoxy sulfonate, and sodium mercaptoimidazole propane sulfonate; Additive B is a brightener, and its specific ingredients include sodium polydisulfide propane sulfonate (SPS), sodium phenyl disulfide propane sulfonate (BSP), sodium alcoholthiopropane sulfonate (HP), and sodium polydimethylamide sulfonate; (6) Preparation of functional current collector Spraying an inorganic nanoparticle solution on the surface of the thickened copper layer to obtain a semi-finished product, drying the semi-finished product, and then washing the dried semi-finished product with a cleaning solution at 23° C. for 15 s and drying to obtain the functional current collector of this embodiment; The solvent used in the inorganic nanoparticle solution is ethanol, the inorganic nanoparticles used in the inorganic nanoparticle solution are nano-silicon dioxide with a particle size of 15 nm, and the mass fraction of nano-silicon dioxide in the inorganic nanoparticle solution is 10%; The cleaning solution is prepared by mixing surfactant fatty alcohol polyoxyethylene ether and water in a mass ratio of 1:10.
[0034] Example 2 This embodiment provides a functional current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step (4) of the functional current collector, the thickness of the nickel-chromium alloy layer is 5 nm; in the preparation step (6) of the functional current collector, the particle size of the inorganic nanoparticle nano-silicon dioxide used in the inorganic nanoparticle solution is 10 nm, and the mass fraction of the nano-silicon dioxide in the inorganic nanoparticle solution is 5%. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0035] Example 3 This embodiment provides a functional current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step (4) of the functional current collector, the thickness of the nickel-chromium alloy layer is 15 nm; in the preparation step (6) of the functional current collector, the particle size of the inorganic nanoparticle nano-silicon dioxide used in the inorganic nanoparticle solution is 20 nm, and the mass fraction of the nano-silicon dioxide in the inorganic nanoparticle solution is 15%. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0036] Example 4 This embodiment provides a functional current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step (6) of the functional current collector, the inorganic nanoparticles used in the inorganic nanoparticle solution are nano-alumina with a particle size of 15 nm. Except for the above difference, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0037] Example 5 This embodiment provides a functional current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step (6) of the functional current collector, the inorganic nanoparticles used in the inorganic nanoparticle solution are nano iron powders with a particle size of about 15 nm. Except for the above difference, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0038] Example 6 This embodiment provides a functional current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step (6) of the functional current collector, the inorganic nanoparticles used in the inorganic nanoparticle solution are nano-nickel powders with a particle size of about 15 nm. Except for the above difference, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0039] Example 7 This embodiment provides a functional current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step (6) of the functional current collector, the solvent used in the inorganic nanoparticle solution is acetone. Except for the above difference, the materials, formula ratio and preparation operation used in this embodiment are strictly consistent with those in the embodiment 1.
[0040] Example 8 This embodiment provides a functional current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step (6) of the functional current collector, the solvent used in the inorganic nanoparticle solution is water. Except for the above difference, the materials, formula ratio and preparation operation used in this embodiment are strictly consistent with those in the embodiment 1.
[0041] Example 9 This embodiment provides a functional current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step (6) of the functional current collector, the solvent used in the inorganic nanoparticle solution is ethyl acetate. Except for the above difference, the materials, formula ratio and preparation operation used in this embodiment are strictly consistent with those in the embodiment 1.
[0042] Example 10 This embodiment provides a functional current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step (6) of the functional current collector, the solvent used in the inorganic nanoparticle solution is xylene. Except for the above difference, the materials, formula ratio and preparation operation used in this embodiment are strictly consistent with those in the embodiment 1.
[0043] Embodiment 11 This embodiment provides a functional current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step (6) of the functional current collector, the mass fraction of nano-silicon dioxide in the inorganic nano-particle solution is 3%. Except for the above difference, the materials, formula ratio and preparation operation used in this embodiment are strictly consistent with those in the embodiment 1.
[0044] Example 12 This embodiment provides a functional current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step (6) of the functional current collector, the mass fraction of nano-silicon dioxide in the inorganic nano-particle solution is 18%. Except for the above difference, the materials, formula ratio and preparation operation used in this embodiment are strictly consistent with those in the embodiment 1.
[0045] Example 13 This embodiment provides a functional current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step (6) of the functional current collector, the particle size of the nano-silicon dioxide used in the inorganic nano-particle solution is 5 nm. Except for the above difference, the materials, formula ratio and preparation operation used in this embodiment are strictly consistent with those in the embodiment 1.
[0046] Embodiment 14 This embodiment provides a functional current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step (6) of the functional current collector, the particle size of the nano-silicon dioxide used in the inorganic nano-particle solution is 30 nm. Except for the above difference, the materials, formula ratio and preparation operation used in this embodiment are strictly consistent with those in the embodiment 1.
[0047] Embodiment 15 This embodiment provides a functional current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step (4) of the functional current collector, the thickness of the nickel-chromium alloy layer is 3 nm. Except for the above difference, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0048] Example 16 This embodiment provides a functional current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step (4) of the functional current collector, the thickness of the nickel-chromium alloy layer is 18 nm. Except for the above difference, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0049] Embodiment 17 This embodiment provides a functional current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step (4) of the functional current collector, the metal layer prepared by magnetron sputtering does not contain a nickel-chromium alloy layer. Except for the above difference, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0050] Comparative Example 1 This comparative example provides a functional current collector. Compared with Example 1, the difference in structure is that in the preparation step (6) of the functional current collector, the operation of spraying the inorganic nanoparticle solution on the surface of the thickened copper layer is omitted. Except for the above difference, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.
[0051] Test Case 1. Participants In this test example, the functional current collectors prepared in Examples 1 to 17 and Comparative Example 1 were used as test objects to conduct relevant performance tests.
[0052] 2. Test content (1) Tensile strength and elongation a. Testing equipment: universal material testing machine b. Sample preparation: Cut the functional current collector to obtain the sample, ensuring that the sample surface is flat and has no obvious oxidation and contamination.
[0053] c. Testing steps: Install the sample on the fixture of the universal material testing machine, ensure that the fixture clamps the sample and the sample is in a vertical state, and will not slip or twist during the test, set the parameters of the testing machine; start the testing machine and stretch the sample; the testing machine will record the force and displacement data during the stretching process in real time; as the stretching progresses, the sample will gradually stretch until it breaks, and record the maximum force value and corresponding displacement at the time of fracture.
[0054] d. Calculation: Calculate the tensile strength and elongation according to the following formula: Tensile strength = maximum force / original cross-sectional area of the specimen; Elongation = (displacement at fracture - initial gauge length) / initial gauge length × 100%.
[0055] (2) Resistivity a. Testing equipment: Four-probe resistivity tester b. Sample preparation: Cut the functional current collector to obtain the sample, ensuring that the sample surface is flat and has no obvious oxidation and contamination.
[0056] c. Test steps: Place the sample on the test platform of the four-probe resistivity tester and ensure that the probes are in good contact with the sample; set the tester parameters and start the tester. The instrument will apply current to the sample through four probes and measure the corresponding voltage value; based on the measured current and voltage values, as well as parameters such as the probe spacing, the instrument will automatically calculate the resistivity of the sample.
[0057] (3) Residual stress The residual stress of the functional current collector is detected by X-ray diffraction (XRD). The specific detection principle is as follows: the residual stress is calculated by measuring the strain of the crystal lattice. When X-rays are irradiated to the crystal, a specific diffraction phenomenon will occur. In the stress-free state, the lattice spacing of the crystal is fixed, and the diffraction peak appears at a specific position. When there is residual stress in the material, the lattice will be strained, resulting in a change in the lattice spacing. This change in the lattice spacing will cause the displacement of the diffraction peak. Therefore, by measuring the displacement of the diffraction peak and combining the elastic constant and other parameters of the material, the strain of the lattice can be calculated. Then, according to the theory of elastic mechanics, the lattice strain is converted into residual stress. Specifically, residual stress will cause changes in the spacing between certain crystal planes of the crystal, thereby changing the diffraction angle. According to Bragg's law: nλ=2d×sinθ (where n is the diffraction order, λ is the wavelength of the X-ray, d is the crystal plane spacing, and θ is the diffraction angle), when d changes, θ will also change accordingly. By accurately measuring the change in the diffraction angle, the magnitude and direction of the residual stress can be calculated.
[0058] 3. Experimental results Table 1. Test results of relevant performance of functional current collectors
[0059] The relevant performance test results of the functional current collectors prepared in Examples 1 to 17 and Comparative Example 1 are shown in Table 1.
[0060] By comparison, it is found that the residual stress of the functional current collectors prepared in Examples 1 to 17 is lower than that in Comparative Example 1. The reason for the above phenomenon is that in the preparation process of the functional current collector in Comparative Example 1, the inorganic nanoparticle solution was not sprayed on the surface of the thickened copper layer, while in the preparation process of the functional current collector in Examples 1 to 17, the inorganic nanoparticle solution was sprayed on the surface of the thickened copper layer. The inorganic nanoparticles contained in the inorganic nanoparticle solution have a high specific surface area and surface activity. In the process of spraying the inorganic nanoparticle solution on the surface of the metal layer, the inorganic nanoparticles contained therein can form good contact and interaction with the surface of the metal layer and change the microstructure of the metal layer, increasing the number of defects and dislocations on the surface of the metal layer. These defects and dislocations can serve as stress concentration points, making the functional current collector The stress is dispersed and released at these positions, thereby reducing the overall stress level of the functional current collector. In addition, the interface bonding force between the inorganic nanoparticles and the metal layer is weak. During the spraying process or when subjected to other external stresses, the inorganic nanoparticles are prone to slight sliding and deformation at the interface between them and the metal layer, which is conducive to absorbing or releasing stress and can play a good buffering role. Therefore, in the preparation process of the functional current collector, by spraying the inorganic nanoparticle solution on the surface of the metal layer (copper layer), the stress can be effectively released from the aspects of microstructure and interface characteristics, thereby achieving the purpose of reducing the residual stress of the functional current collector and improving the stability, mechanical strength and electrochemical properties of the functional current collector.
[0061] Compared with Example 1, the inorganic nanoparticles in the inorganic nanoparticle solution used in the preparation process of the functional current collector in Examples 5 and 6 are nano-iron powder and nano-nickel powder, respectively. The test results show that the residual stress and resistivity of the functional current collector provided by Examples 5 and 6 are higher than those in Example 1, and the tensile strength and elongation are lower than those in Example 1. This is mainly because the chemical properties of nano-iron powder and nano-nickel powder are relatively active, and they are easily oxidized or undergo unnecessary chemical reactions with the metal layer during use, thereby affecting the mechanical strength and electrochemical properties of the functional current collector. In addition, the specific surface area and surface activity of nano-iron powder and nano-nickel powder are not as good as those of nano-silicon dioxide and nano-alumina, and the contact and interaction effects with the surface of the metal layer are poor, and the dispersion and release effects on stress are not obvious.
[0062] Compared with Examples 1 and 7, the inorganic nanoparticle solutions used in Examples 8, 9, and 10 in the preparation process of the functional current collector use water, ethyl acetate, and xylene as solvents, respectively. The test results show that the residual stress and resistivity of the functional current collectors prepared in Examples 8, 9, and 10 are higher than those in Examples 1 and 7, and the tensile strength and elongation are lower than those in Examples 1 and 7. This is mainly because the inorganic nanoparticle solutions used in the preparation process of the functional current collectors in Examples 1 and 7 use ethanol or acetone as solvents. Ethanol and acetone have certain volatility but do not evaporate too quickly. In the process of spraying the inorganic nanoparticle solution using ethanol or acetone as solvent on the surface of the metal layer, ethanol and / or acetone can be evenly distributed on the surface of the metal layer. Such evenly distributed inorganic nanoparticles can effectively hinder the regular arrangement of metal atoms in the metal layer and reduce the accumulation of internal stress. The inorganic nanoparticle solution used in the preparation process of the functional current collector in Example 8 uses water as solvent. Due to the large surface tension of water, the inorganic nanoparticle solution used in the preparation process of the functional current collector is more uniform. During the preparation process, it is difficult for the inorganic nanoparticles to be evenly distributed on the surface of the metal layer, resulting in agglomeration of the inorganic nanoparticles, making it difficult to effectively penetrate and cover the surface of the metal layer, which in turn causes the residual stress of the functional current collector to be higher than that of Examples 1 and 7; in Example 9, the inorganic nanoparticle solution used in the preparation process of the functional current collector uses ethyl acetate as the solvent. Due to the excessive volatility of ethyl acetate, during the preparation process of the functional current collector, the inorganic nanoparticles gather together too quickly before the solvent completely evaporates, making it difficult for the inorganic nanoparticles to be evenly distributed on the surface of the metal layer, which will cause the action range of the inorganic nanoparticles to be reduced and uneven, making it difficult to effectively reduce the overall stress level of the functional current collector finally obtained; in Example 10, the inorganic nanoparticle solution used in the preparation process of the functional current collector uses xylene as the solvent. Due to the weak volatility of xylene, during the preparation process of the functional current collector, the inorganic nanoparticles are difficult to be compounded and fixed on the surface of the metal layer in a timely manner, affecting the stress release effect of the functional current collector.
[0063] Compared with Example 1, the mass fractions of nano-silicon dioxide in the inorganic nanoparticle solution used in the preparation process of the functional current collector in Examples 11 and 12 are 3% and 18%, respectively. The test results show that the residual stress and resistivity of the functional current collectors provided by Examples 11 and 12 are higher than those in Example 1, and the tensile strength and elongation are lower than those in Example 1. This is mainly because in the preparation process of the functional current collector in Example 1, the mass fraction of inorganic nanoparticles in the inorganic nanoparticle solution sprayed on the surface of the metal layer is controlled within the range of 5-15%, which can provide sufficient stress concentration points and defects on the surface of the metal layer, so that the residual stress generated in the preparation process of the functional current collector is well dispersed and released, and the inorganic nanoparticles can be evenly dispersed in the solution, so that the inorganic nanoparticles can be evenly attached to the surface of the metal layer during the process of spraying the inorganic nanoparticle solution on the surface of the metal layer, thereby improving the residual stress release effect of the functional current collector; while the mass fraction of inorganic nanoparticles in the inorganic nanoparticle solution used in the preparation process of the functional current collector in Example 11 is too low, which will lead to This results in an insufficient number of stress concentration points and defects provided by the inorganic nanoparticles, making it difficult to effectively disperse and release the stress generated by the functional current collector during the preparation process, thereby making it difficult to achieve an ideal stress release effect. Second, too few inorganic nanoparticles can hardly fully change the microstructure of the functional current collector, so that the inorganic nanoparticles have an unobvious hindering effect on the regular arrangement of metal atoms in the metal layer of the functional current collector, and have a limited effect on reducing internal stress accumulation, which in turn leads to an unsatisfactory residual stress reduction effect of the functional current collector. In Example 12, the mass fraction of inorganic nanoparticles in the inorganic nanoparticle solution used in the preparation process of the functional current collector is too high. First, it is easy to cause the nanoparticles to agglomerate in the solution, making it difficult to disperse evenly. The agglomerated inorganic nanoparticles are difficult to evenly cover the surface of the metal layer of the functional current collector, affecting the stress release effect of the functional current collector finally obtained. Second, too many inorganic nanoparticles will increase the viscosity of the inorganic nanoparticle solution, making it difficult to evenly adhere to the surface of the metal layer of the functional current collector during the spraying process, thereby resulting in uneven local stress release of the functional current collector finally obtained.
[0064] Compared with Example 1, the particle sizes of the inorganic nanoparticles in the inorganic nanoparticle solution used in Examples 13 and 14 during the preparation of the functional current collector are 5 nm and 30 nm, respectively. The test results show that the residual stress and resistivity of the functional current collectors provided by Examples 13 and 14 are higher than those of Example 1, and the tensile strength and elongation are lower than those of Example 1. This is mainly because the particle size of the inorganic nanoparticles in the inorganic nanoparticle solution used in the preparation of the functional current collector in Example 1 meets the requirement of 10 to 20 nm. nm, the inorganic nanoparticles meeting the above range have good dispersibility, moderate surface activity, and good penetration and filling ability, which can ensure the uniform distribution of the inorganic nanoparticles on the surface of the metal layer, so that the inorganic nanoparticles can effectively interact with the surface of the metal layer of the functional current collector, and can reduce the risk of instability or overreaction of the inorganic nanoparticles due to excessive surface activity of the inorganic nanoparticles. They can penetrate into the microstructure of the functional current collector to a certain extent, fill the tiny gaps therein, enhance the overall structural stability and performance of the functional current collector, and play the role of stress release; Example 13 The particle size of the inorganic nanoparticles in the inorganic nanoparticle solution used in the preparation process of the functional current collector is too small, and the surface of the inorganic nanoparticles with too small a particle size is too small. If the surface energy is too high, its stability in the solvent will decrease, and it will be easy to agglomerate or precipitate. If the particle size is too small, the penetration depth of the inorganic nanoparticles in the functional current collector will be too great, which will make it difficult for the inorganic nanoparticles to play a stress release role in the metal layer. In Example 14, the particle size of the inorganic nanoparticles in the inorganic nanoparticle solution used in the preparation process of the functional current collector is too large. The inorganic nanoparticles with too large a particle size have poor dispersion performance in the solvent and are easy to agglomerate in the solvent, resulting in a decrease in the uniformity of the inorganic nanoparticles, thereby affecting the distribution uniformity of the inorganic nanoparticles on the surface of the metal layer of the functional current collector and the effect of stress release. In addition, inorganic nanoparticles with too large a particle size will affect the uniformity of the microstructure of the functional current collector, thereby affecting its overall mechanical properties.
[0065] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. A method for preparing a functional current collector, characterized in that: The following steps are involved: S1. Plating a metal layer on at least one surface of the base film by magnetron sputtering; S2. spraying an inorganic nanoparticle solution on the surface of the metal layer to obtain a semi-finished product; S3. Drying the semi-finished product to obtain the functional current collector.
2. The method for preparing the functional fluid collector according to claim 1, characterized in that: In S2, the inorganic nanoparticles in the inorganic nanoparticle solution include at least one of nano-silicon dioxide, nano-aluminum oxide, nano-iron powder, and nano-nickel powder.
3. The method for preparing the functional fluid collector according to claim 2, characterized in that: In S2, the inorganic nanoparticles in the inorganic nanoparticle solution include at least one of nano-silicon dioxide and nano-aluminum oxide.
4. The method for preparing the functional current collector according to claim 1, characterized in that: In S2, the particle size of the inorganic nanoparticles in the inorganic nanoparticle solution is 10-20 nm.
5. The method for preparing the functional fluid collector according to claim 1, characterized in that: In S2, the mass fraction of the inorganic nanoparticles in the inorganic nanoparticle solution is 5-15%.
6. The method for preparing the functional current collector according to claim 1, characterized in that: In S2, the solvent in the inorganic nanoparticle solution includes at least one of ethanol and acetone.
7. The method for preparing the functional fluid collector according to claim 1, characterized in that: In S3, after the semi-finished product is dried, the step of washing the semi-finished product after drying with a washing liquid is also included; The cleaning solution contains a surfactant, and the surfactant includes fatty alcohol polyoxyethylene ether.
8. The method for preparing the functional current collector according to claim 7, characterized in that: The cleaning conditions are as follows: time 10-20 s, temperature 20-25°C.
9. The method for preparing the functional current collector according to claim 1, characterized in that: In S1, along the direction away from the base film, the metal layer includes a nickel-chromium alloy layer and a copper layer which are compounded in sequence.
10. A functional fluid collector, characterized in that: The functional current collector is prepared by the preparation method of the functional current collector according to any one of claims 1 to 9.
Citation Information
Patent Citations
Composite copper foil current collector, preparation method thereof and lithium ion battery
CN118380589A
Composite current collector and preparation method and application thereof
CN118867260A
Multilayer structure mass flow body
CN207097948U
Lithium-ion secondary battery
IN202017054485A